Accurate Reference Gas Mixtures Containing Tritiated Molecules: Their Production and Raman-Based Analysis - Simon Niemes; Helmut H. Telle; Beate Bornschein; Lucian Fasselt; Robin Größle; Florian Priester; Magnus Schlösser; Michael Sturm; Stefan Welte; Genrich Zeller (Sensors, 2021)
Highly accurate, quantitative analyses of mixtures of hydrogen isotopologues—both the stable species, H2, D2, and HD, and the radioactive species, T2, HT, and DT—are of great importance in fields as diverse as deuterium–tritium fusion, neutrino mass measurements using tritium β-decay, or for photonuclear experiments in which hydrogen–deuterium targets are used. In this publication we describe a production, handling, and analysis facility capable of fabricating well-defined gas samples, which may contain any of the stable and radioactive hydrogen isotopologues, with sub-percent accuracy for the relative species concentrations. The production is based on precise manometric gas mixing of H2, D2, and T2. The heteronuclear isotopologues HD, HT, and DT are generated via controlled, in-line catalytic reaction or by β-induced self-equilibration, respectively. The analysis was carried out using an in-line intensity- and wavelength-calibrated Raman spectroscopy system. This allows for continuous monitoring of the composition of the circulating gas during the self-equilibration or catalytic evolution phases. During all procedures, effects, such as exchange reactions with wall materials, were considered with care. Together with measurement statistics, these and other systematic effects were included in the determination of composition uncertainties of the generated reference gas samples. Measurement and calibration accuracy at the level of 1% was achieved.